Instantaneous wave‐free ratio‐guided revascularization of nonculprit lesions in STEMI patients with multivessel coronary disease: The WAVE registry. Issue 3 (23rd July 2022) - Musto, Carmine; Scappaticci, Massimiliano; Biondi‐Zoccai, Giuseppe; De Felice, Francesco; D'Amario, Domenico; Nazzaro, Marco S.; Stio, Rocco E.; Del Prete, Armando; Chin, Diana; Pennacchi, Mauro; Paolucci, Luca; Versaci, Francesco; et al.
Abstract: Background: Complete revascularization (CR) of nonculprit lesions (NCL) is strongly recommended in patients with ST‐elevation myocardial infarction (STEMI) and multivessel coronary artery disease (MVD), but no definitive evidence is available regarding which diagnostic strategy should be preferred. Instantaneous wave‐free ratio (iFR) has never been investigated in this setting. We aimed to describe clinical outcomes of a cohort of patients undergoing iFR‐guided CR. Methods: Following primary percutaneous coronary intervention (PCI), consecutive patients with STEMI and intermediate NCL were enrolled and destinated to an iFR‐guided CR. NCL with iFR ≤ 0.89 underwent PCI while NCL with iFR > 0.89 were deferred. The primary endpoint was NC target lesion failure (NC‐TLF) and the secondary endpoint was major adverse cardiovascular events (MACE), at 1‐year follow‐up. Results: Overall, 209 patients were enrolled (ischemic iFR = 83; nonischemic iFR = 126). Patients with ischemic iFR showed a higher prevalence of traditional cardiovascular risk factors and angiographically determined three‐vessel disease. In the entire cohort, NC‐TLF and MACE occurred in 6.7% and 10.5% of patients, respectively. Compared to the deferred group, patients with ischemic iFR experienced significantly higher rates of both NC‐TLF (3.2% vs. 12.1%; p  = 0.021) and MACE (7.1% vs. 16.9%; p  = 0.041). These results were mostly driven by increased rates of NC‐TLF PCI and further revascularizations in this latter group, while no differences were evident in terms of nonfatal myocardial infarction or death. At multivariable analysis, the strongest predictor of MACE was symptom onset to balloon time (HR = 1.17 [95% CI: 1.04–1.31], p  = 0.008). Conclusions: In our study enrolling STEMI patients with MVD, iFR assessment was feasible and safe. PCI‐deferring according to iFR evaluation of NCL was associated with low rates of adverse events. Further randomized studies are needed to investigate the effectiveness of iFR‐guided revascularization compared to current practice in this setting.